Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting, November 24, 2008. (Policy Papers; Policy Paper, 2008)
The global economy is going through a period of unprecedented financial instability. The Fund has been asked by the IMFC to play a leading role in helping the membership both to deal with the immediate crisis and work towards a new strengthened global architecture. These tasks are well within our mandate. Addressing these challenges-and doing so within a compressed timeframe-will require strict prioritization on three key areas: (i) providing policy advice and timely financial support that meets members' needs; (ii) understanding what went wrong; (iii) and assembling the building blocks of a new international financial architecture.